P049 Development of human embryonic stem cell-derived intestinal organoids for in vitro studies on intestinal inflammation and fibrosis. (27th May 2021) - Kandilogiannakis, L; Filidou, E; Drygiannakis, I; Tarapatzi, G; Arvanitidis, K; Bamias, G; Valatas, V; Paspaliaris, V; Kolios, G
Abstract: Background: Organoids are self-renewing, 3D structures, consisting of different cell types, with histology and physiology features very close to the physiology of the studied organ. Specifically, human Intestinal Organoids (HIOs) develop epithelial crypts consisting of all subtypes of intestinal epithelial cells which are surrounded by mesenchymal cells. Our aim was to develop 3D HIOs from human embryonic stem cells (hESCs) and examine the expression of fibrotic and mesenchymal factors during their maturation process. Additionally, we investigated the effect of the pro-inflammatory cytokines, IL-1α and TNF-α on the expression of fibrotic and inflammatory mediators in HIOs. Methods: The human ESC line (H1) was cultured and then differentiated towards HIOs using commercially available kit. HIOs were characterized by immunofluorescence in all differentiation stages. In order to examine their maturation process, we compared the mRNA expression of fibrotic and mesenchymal markers from passages 1–10. In order to examine their functionality, HIOs from different passages were stimulated with 5ng/ml IL-1α and 50ng/ml TNF-α for 12 hours, total RNA was collected and the fibrotic and inflammatory mRNA expression was examined. The mRNA transcripts of CD90, collagen type I, III, fibronectin, CXCL8, CXCL10 and CXCL11 were measured by reverse transcription quantitative PCR. Results: HIOs were successfully developed as they were stained positive for all tested markers throughout their developmental process. Regarding their maturation process, we observed high expression of CD90, collagen type I, type III and fibronectin that was gradually decreased during passages. As for the fibrotic and inflammatory responses from HIOs, we found that the IL-1α and TNF-α stimulation resulted in statistically significant upregulation of the fibrotic factors, fibronectin, collagen type I and type III in culture passages 2 and 4, but had no effect in culture passages 8 and 10. Similarly, IL-1α and TNF-α stimulation led to the statistically significant induction of the inflammatory chemokines CXCL8, CXCL10 and CXCL11 in culture passages 2 and 4, while no effect was observed in culture passages 8 and 10. Conclusion: Our findings indicate that HIOs contain a functional mesenchymal component that is gradually diminished during passages. Inflammatory and fibrotic responses of HIOs seem to depend on the fitness of their mesenchyme. IBD studies using HIOs as in vitro models should be performed on early passages, when HIO's mesenchymal component is still functional.